Does the I86F mutation of succinate dehydrogenase subunit c increase fungicide resistance and have a fitness in Asian Soybean Rust (Phakopsora pachyrhizi)? - Borba, Jackeline Pedriana (2020)
Asian Soybean Rust (ASR) is the most economically important soybean disease worldwide, and can cause yield losses of up to 80%. Brazil is the second largest producer and the most important soybean exporter (CONAB, 2018), therefore any constraints to soybean production have a negative impact on the national economy. ASR management relies mainly in fungicide application, but lower sensitivity for all the current mode of action fungicides has been reported. Of twenty active ingredients that comprise the SDHI fungicides, only three of these are labeled for soybean rust disease control. The limited availability of chemical groups for ASR disease control and the resourcing time to discovery, development and registration of new fungicides makes the fungicide resistance management critical for soybean crop production. Genetic structure is of importance to understand and predict the potential for pathogen populations to evolve and adapt in agricultural ecosystems. Three contrasting strains for SDHI sensitivity - 100% I86 susceptible (S); 50% I86/50% 86F resistant (R); 100% 86F resistant - were obtained by selecting survival uredinia at high carboxamide doses. The level of resistance was determined by EC50 in detached leaf assay. Higher I86F frequencies were associated with higher SDHI concentrations. Benzovindiflupyr and Fluxapyroxad are cross resistant between each other, but EC50 values for mutants strains increased less for Fluxaproxad than for Benzovindiflupyr. Mutant strains showed a faster initial development compared with the wild- type strain, with faster germination and appressorium development, increasing the chance of successful infection. Shorter latent period and higher disease severity was observed for the heterokaryotic (H) strain when compared with both 86F (R) and I86 (S) strains. Despite the faster initial development and virulence, resistant (R) strains showed a competitive disadvantageous when mixed with the wild type (S) strains. A decrease in 86F frequency was observed during five disease cycles. The frequency of 86F allele is stable in pure culture over five disease cycles in non-treated soybean leaves.